Are recent health, welfare and care graduates part of a rural and remote workforce solution? Evidence from Tasmania, Australia - Belinda Jessup; Fiona Proudfoot; Merylin Cross; Tony Barnett (BMC, 2024)
Abstract Background Strong growth in graduate supply from health, welfare and care courses across Australia may bode well for easing rural workforce shortages. However, little is known about the employment opportunities available for recent graduates in non-metropolitan areas. This study aimed to quantify and describe advertised job vacancies for health, welfare and care professions in Tasmania, a largely rural and geographically isolated island state of Australia. Further, it aimed to examine those job vacancies specifying that recent graduates were suitable to apply. Methods Job advertisements for health, welfare and care professionals were collected weekly throughout 2018 from six online job vacancy websites. Data were extracted on 25 variables pertaining to type of profession, number of positions, location, and graduate suitability. Location of positions were recoded into a Modified Monash Model (MM) category, the Australian geographic standard used to classify rurality. Positions advertised in MM2 areas were considered regional and MM3-7 areas rural to very remote. Data were analysed using descriptive and inferential statistics. Results Over the twelve-month period, 3967 advertisements were identified, recruiting for more than 4700 positions across 49 different health, welfare and care professions in Tasmania. Most vacancies were in the non-government sector (58.5%) and located in regional areas (71.7%) of the state. Professions most frequently advertised were registered nurse (24.4%) and welfare worker (11.4%). Eleven professions, including physiotherapist and occupational therapist, recorded a disproportionate number of advertisements relative to workforce size, suggesting discipline specific workforce shortages. Only 4.6% of collected advertisements specified that a recent graduate would be suitable to apply. Of these, most were for the non-government sector (70.1%) and located in regional areas (73.4%). The professions of physiotherapist (26.6%) and occupational therapist (11.4%) were most frequently represented in advertised graduate suitable positions. Conclusions Despite a range of advertised employment opportunities for health, welfare and care professionals across Tasmania, few specified vacancies as suitable for recent graduates and most were located in regional areas of the state. Health, welfare and care services in non-metropolitan locations may need to develop more employment opportunities for recent graduates and explicitly advertise these to job-seeking graduates to help grow and sustain the rural and remote health workforce into the future.